2021
DOI: 10.1002/alz.12447
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic plasma biomarkers for preclinical Alzheimer's disease

Abstract: Introduction:This study involved a parallel comparison of the diagnostic and longitudinal monitoring potential of plasma glial fibrillary acidic protein (GFAP), total tau (t-tau), phosphorylated tau (p-tau181 and p-tau231), and neurofilament light (NFL) in preclinical Alzheimer's disease (AD).Methods: Plasma proteins were measured using Simoa assays in cognitively unimpaired older adults (CU), with either absence (Aβ−) or presence (Aβ+) of brain amyloidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
117
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(143 citation statements)
references
References 44 publications
21
117
1
4
Order By: Relevance
“…In recent years, many studies have reported the close relationship between GFAP and AD. Chatterjee et al [ 33 ]. used Simoa assay to measure plasma proteins in cognitively unimpaired older adults (CU) and found that GFAP and p-tau181 were upregulated in the CU group with cerebral amyloidosis, which indicated the clinical potential of GFAP and p-tau for the diagnosis and longitudinal monitoring of preclinical AD.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many studies have reported the close relationship between GFAP and AD. Chatterjee et al [ 33 ]. used Simoa assay to measure plasma proteins in cognitively unimpaired older adults (CU) and found that GFAP and p-tau181 were upregulated in the CU group with cerebral amyloidosis, which indicated the clinical potential of GFAP and p-tau for the diagnosis and longitudinal monitoring of preclinical AD.…”
Section: Discussionmentioning
confidence: 99%
“…The repeatability and reproducibility of the test method should also be checked. Recently, the ultrasensitive immunoassay technique (single-molecule array, Simoa) has achieved great progress in the sensitive detection of plasma A β and p-tau ( Chatterjee et al, 2021 ). However, early and effective diagnosis of AD remains a challenge due to the complexity of AD pathogenesis, which leads to production of several related biomarkers and lack of reproducibility.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Most p‐tau assays target tau phosphorylated at T181 (p‐tau181), yet tau hyperphosphorylation in AD involves several phosphorylation sites and recently two additional p‐tau species, p‐tau217 and p‐tau231, have gained increased attention 7 . While some studies reported comparable performances, 8–10 others suggested earlier elevations of p‐tau217 and p‐tau231 as well as slightly better performances to detect asymptomatic Aβ pathology relative to p‐tau181 6,10–13 . However, a limitation of these studies is the use of the antibody AT270 for plasma p‐tau181 quantification, which cross‐reacts with p‐tau175, thus limiting assay specificity 14 .…”
Section: Introductionmentioning
confidence: 99%